9th EASN International Conference on Innovation in Aviation & Space - Pantelakis, Spiros; Strohmayer, Andreas (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue book contains selected papers from works presented at the 9th EASN (European Aeronautics Science Network) International Conference on Innovation in Aviation & Space, which was held in Athens, Greece from the 3rd until the 6th of September, 2019. About 450 participants contributed to a high-level scientific gathering, providing some of the latest research results on the topic, as well as some of the latest relevant technological advancements. Eight interesting articles, which cover a wide range of topics including characterization, analysis and design, as well as numerical simulation, are contained in this Special Issue.